Rangeland management and animal production sustainability under arid and semi arid conditions: Egypt overview - Taha E.A.; Khidr R.E. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
Livestock fodder needs in nearly all developing countries now exceed the sustainable yield of rangelands and other forage resources. In Africa, overgrazing has reduced range productivity virtually everywhere. It is important to provide animals with adequate nutrition to ensure the high productive and reproductive performance. Meanwhile, it is necessary to avoid the deterioration of the pastureland from the grazing pressure; some procedures should be carried out to ensure the integration and balancing of the biosystem elements such as determining the suitable carrying capacity and stocking rate of the rangeland, use of suitable grazing system, multi species grazing, optimizing pasture utilization and supplemental feeding.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)